Fluorescence of chlorophyll a in pineapple plants submitted to herbicide applications - Corrêa, Juliano Miari; Ferreira, Evander Alves; Pereira, Gustavo Antônio Mendes; Piratoba, Alba Rocio Aguilar; Santos, José Barbosa dos; Oliveira, Carlos Henrique de; Silva, Cícero Teixeira (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The chemical management of weeds with herbicides is recommended for crops, a strategy that allows for the effective control of pineapple crops and that can affect growth and physiology. Accordingly, the objective of this study was to evaluate the effect of post-emergence herbicides on the fluorescence parameters chlorophyll and electron transport rate, relating chlorophyll a fluorescence in pineapple plants, Imperial variety, and checking for poisoning caused by these products. This experiment was carried out in the field in randomized blocks in a 5x2 factorial scheme, with four herbicides (ametym, diuron, fluazifop and sulfentrazone), a control (without herbicide) and two evaluation times (7 and 21 days after the application). The chlorophyll fluorescence monitoring and electron transport rates were carried out 7 and 21 days after the application of the treatment. The variables were: 1) initial fluorescence; 2) maximum fluorescence; 3) variable fluorescence ratio and total fluorescence; and 4) electron transport rate. The evaluated herbicides negatively affected the photosynthetic apparatus of the pineapple plants. The herbicide diuron, followed by ametrym, caused the greatest physiological stress in the crop. In the second evaluation period, the effects on the photosynthetic apparatus of the plants intensified, where the tested products reduced the values of the variables and maximum fluorescence ratio, indicating increased stress from the evaluated herbicides.